2016
DOI: 10.1002/ajoc.201600241
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Catalyzed Oxidative Dimerization of 2‐Phenylpyridine Derivatives

Abstract: The oxidative dimerizationo f2 -phenylpyridine derivatives using cobalt catalysis is reported. Three types of reaction conditions were developed with different loadings of cobalt catalyst. Cross couplingo ft wo different 2arylpyridines using cobalt catalysis proceeded with modest yields and selectivity.The biaryl moiety is one of the most important privileged structures in medicinal chemistry and is prevalent in al arge number of pharmaceuticals and biologically active molecules. [1] Many methods have been dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…We also wish to mention previous example of this type of complex reported by Xie et al in 2016. 15 In this report Xie et al were able to isolate a structure with the biaryl coupling and acetylacetanoate in the 5 th and 6 th coordination spheres.…”
Section: Formation Of the Co III (Pivo)(bqn-bqn) And Co Ii (Bqn-bqn) mentioning
confidence: 95%
See 2 more Smart Citations
“…We also wish to mention previous example of this type of complex reported by Xie et al in 2016. 15 In this report Xie et al were able to isolate a structure with the biaryl coupling and acetylacetanoate in the 5 th and 6 th coordination spheres.…”
Section: Formation Of the Co III (Pivo)(bqn-bqn) And Co Ii (Bqn-bqn) mentioning
confidence: 95%
“…Complex 4 adds to the small number of isolable Co(III)-aryl complexes prepared via direct C-H insertion. 15,29,[32][33][34] Inspired by these experimental ndings, we extended our computational studies to explore the reactivity of [Co(BQN) 2 (PivO)], 1a. We found that this complex possesses a trigonal bipyramid geometry (see Fig.…”
Section: Initial Complex Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Over the past decade,i nsitu generated low-valent cobalt catalysts have been utilized in C À H arylation of arenes with aryl Grignard reagents,a ryl halides, and phenol derivatives in the presence of Grignard reagents as the bases and reductants. [7] In contrast, the bidentate directing strategy using the relatively cheap Cp*-free (Cp* = C 5 Me 5 )C oX n (n = 2, 3) salts as catalysts has become apromising methodology for C À Hb ond functionalization. [7] In contrast, the bidentate directing strategy using the relatively cheap Cp*-free (Cp* = C 5 Me 5 )C oX n (n = 2, 3) salts as catalysts has become apromising methodology for C À Hb ond functionalization.…”
mentioning
confidence: 99%
“…[6] However,t ot he best of our knowledge,n oc obalt-catalyzed cross-coupling reaction between two aryl CÀHb onds has been developed so far. [7] In contrast, the bidentate directing strategy using the relatively cheap Cp*-free (Cp* = C 5 Me 5 )C oX n (n = 2, 3) salts as catalysts has become apromising methodology for C À Hb ond functionalization. [8] Recently,c obalt-catalyzed C(sp 2 ) À Hamination and alkoxylation, assisted by abidentate directing group,w as described by our group.…”
mentioning
confidence: 99%